STUDENT-CENTERED LEARNING IN CONTEMPORARY EDUCATION - Ko`shkinova Aynash Garifulla Qizi; Khamitov Eldorbek Erkinovich (TADQIQOTLAR, 2026)
ABSTRACT: Student-centered learning has become one of the most influential approaches in contemporary education, responding to the growing demand for learners who  are  autonomous,  critical,  and  adaptable.  Unlike  traditional  teacher-centered instruction,  student-centered  learning  places  learners  at  the  core  of  the  educational process, encouraging active participation, self-directed learning, and responsibility for one’s  own  academic  development.  This  article  examines  the  concept  of  student-centered learning, its theoretical foundations, key principles, and educational benefits. Based on an analytical review of pedagogical theories and empirical research, the study provides an original academic discussion of how student-centered learning contributes to academic success, motivation, and lifelong learning skills. The findings indicate that student-centered learning is an essential component of modern education systems and plays a significant role in preparing students for the challenges of the contemporary world.